Encyclopedia of the solar system / edited by Tilman Spohn, Institut of Planetary Research, German Aerospace Centre (DLR), Berlin, Germany, Doris Breuer, Institut of Planetary Research, German Aerospace Centre (DLR), Berlin, Germany, Torrence Johnson, Jet Propulsion Laboratory, NASA, Pasadena, CA, USA.
The Encyclopedia of the Solar System, Third Edition―winner of the 2015 PROSE Award in Cosmology & Astronomy from the Association of American Publishers―provides a framework for understanding the origin and evolution of the solar system, historical discoveries, and details about planetary bodies and how they interact―with an astounding breadth of content and breathtaking visual impact. The encyclopedia includes the latest explorations and observations, hundreds of color digital images and illustrations, and over 1,000 pages. It stands alone as the definitive work in this field, and will serve as a modern messenger of scientific discovery and provide a look into the future of our solar system.